Impact Assessment of Green Infrastructure in Urban Planning - Teodoro Semeraro (Current Advances in Geography, Environment and Earth Sciences Vol. 9, 2022)
Urbanization produces land use and land cover change with a strong negative impact on the provision of ecosystem services due to the alteration and loss of biological processes and structures of the ecosystems. An important counter-measure could include Nature-based Solutions for improving natural capital in the urban areas and introducing important ecological processes and structures for improving human well-being and creating more livable cities. Tools and strategies able to integrate ecosystem services assessment in urban planning and design represent a new frontier in urban sustainability. In this study, a methodological example of analyzing the impacts of urban planning and design on ecosystem services production at a neighbourhood scale is proposed. The ecosystem services assessment was carried out considering as starting point the land use and land cover of the study area in its current state and after the potential changes in the ecosystem services produced from the evolution of land use and land cover generated by the urban actions planned. The scenario of analysis includes the integrations of Nature-based Solutions in urban planning at a neighbourhood scale. The ecosystem services analysis was focused on considering microclimate and greenhouse gas regulation as priority ecosystem services able to improve the thermal comfort and carbon managament in the new urban scenarios. The case study is located in the municipality of Gallipoli, Southern Italy and it is a peri-urban area characterized by an agroecosystem but planned for an urban expansion. In the current state, the analysis highlights a low ecosystem services production of the agroecosystem characterized mainly by arable land affected by Xylella fastidiosa bacteria that destroy important olive trees. So, the integration of Nature-based Solutions such as urban forests could be a good strategy to improve the thermal comfort and reduce the carbon dioxide concentration in the study area in reference to the current state. The ecosystem services assessment highlighted that the ecological design of Natural based Solutions can improve the typology of ecosystem services production of new urban land use and land cover against the current scenario. Therefore, the capacity to integrate ecosystem services analysis in urban planning could be a tool of the ecological urban design useful to support the decision-making processes.